ANALYSIS OF COMPILING TEXTBOOKS FOR DEVELOPING READING SKILLS IN ARABIC LANGUAGE - Tausiah, Hilma; Rosita, Eros; Amanillah, Sofa; Sauri, Sofyan (EDUTECH, 2019)
Textbooks represent one of the important sources mainly used in teaching and learning contexts. Many teachers compiled textbooks that cube with the national curriculum authorized by the government. Therefore, some of the teacher are not qualified enough to compile such textbook. Texrbooks must be carefully designed in order to be understood Â by readers. The aim of this research was to explore how teacher prepare Arabic textbooks to develop reading skills. Specifically, the main objective of this study was to provide a clear understanding, specify the function, identify the essential techniques, and present the stages or genre of compiling Arabic reading textbooks. The study used a descriptive analytical base on a qualitative approach. The result showed that teachers show ability to compile textbooks properly and correctly in accordance with the function, the techniques and genre of the Arabic textbook of reading skills.Buku teks merupakan salah satu sumber belajar dan bahan ajar yang banyak digunakan dalam pembelajaran oleh setiap pengajar. Bahkan buku teks banyak disusun oleh para pengajarnya sendiri yang disesuaikan dengan kurikulum yang telah disusun oleh pemerintah yang diberi nama kurikulum nasional (Kurnas). Namun pada kenyataannya tidak semua orang mengerti dan paham dalam menyusun buku teks. Maka dari itu, penyusunannya pun perlu diperhatikan dengan cermat agar dapat diterima dan dipahami oleh semua pihak yang berkepentingan. Adapun tujuan umum penelitian ini adalah untuk mengetahui penyusunan buku teks dalam meningkatkan keterampilan membaca bahasa Arab. Sedangkan tujuan khususnya untuk mengetahui pengertian, fungsi, dasar-dasar, landasan dan tahapan buku teks. Metode yang digunakan studi deskriptif Â analisis dengan pendekatan kualitatif. Hasil dari penelitian ini adalah adanya kemampuan untuk menyusun buku teks dengan baik dan benar yang sesuai dengan fungsi, dasar-dasar, landasan dan tahapan buku teks.